Faktor Penyebab Terjadinya Perceraian Dan Akibatnya Terhadap Perkembangan Anak Di Kecamatan Teluk Mutiara Kabupaten Alor - Koteng, Nur Azizah Nilamsari Jakaria; Hedewata, Agustinus; Mauritsius, Darius (Law Faculty, Nusa Cendana University, 2023)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family/household based on the belief in the Almighty God. The problem formulation is (1) What are the factors causing divorce in Teluk Mutiara District, Alor Regency? (2) What are the legal consequences for children's development in Teluk Mutiara District, Alor Regency? The aim of the research is to determine the factors causing divorce in Teluk Mutiara District, Alor Regency and the legal consequences for child development in Teluk Mutiara District, Alor Regency. There are 2 benefits of this research, namely theoretical benefits to provide information and development of the application of legal knowledge, especially in the field of civil law regarding the causes and effects on child development and practical benefits to provide information to the government to socialize to the public about divorce on child development and input for parents. interested parties. The research method used is empirical research. The research results show that: (1) the factors that cause divorce are Domestic Violence (KDRT), infidelity, economic factors. (2) the legal consequences for children's development, namely that children suddenly become quiet, become aggressive, and become less confident. The author's conclusion: the factors that cause divorce in Teluk Mutiara District, Alor Regency, if minimized properly, will not or reduce the occurrence of divorce in the future and will not affect children's development.